Treatment of Homozygous Type II Antithrombin Heparin-Binding Site Deficiency in Pregnancy - Hilde Fiskvik; Anne F. Jacobsen; Nina Iversen; Carola E. Henriksson; Eva-Marie Jacobsen (Case Reports in Obstetrics and Gynecology)
Pregnancy is associated with an increased risk of venous thromboembolism (VTE). Previous VTE and severe thrombophilia are important risk factors. Our case was a 36-year-old woman, gravida 6, para 0, with antithrombin (AT) deficiency caused by a homozygous mutation in the heparin-binding site (HBS). Her history included seven prior VTEs, three early and two late pregnancy losses. She was prophylactically treated with both human plasma-derived AT concentrate (hpATC) and low molecular weight heparin (LMWH), resulting in a successful 6th pregnancy and a healthy live born baby. There is limited evidence and guidance on the management of AT deficiency in pregnancy. Dosing and monitoring of anticoagulants, alone or together with hpATC, must be based on individual risk assessment. The severity of clinical manifestations varies with the type of AT deficiency. Characterization of the AT mutation may aid in the decision-making process and optimize pregnancy outcomes.